Knowledge and Attitude as Factors Affecting Regularity of Antenatal Care Visits - Titania Titania; Elsa Pudji Setiawati; Hadi Susiarno (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Maternal mortality ratio and infant mortality rate in Indonesia are still high and far from the Millennium Development Goals target. One of the solutions is by making regular antenatal care visits. Factors affecting antenatal care are knowledge and attitude. This study aimed to analyze the influence of knowledge and attitude about antenatal care toward regularity of antenatal care visit.Methods: This analytic study was conducted by using the rapid survey through cross-sectional approach. The study population was pregnant women in Cipacing Village, Jatinangor Sub-district, with 55 samples. Questionnaires were distributed to evaluate the knowledge and attitude, and Kartu Menuju Sehat observation was conducted to investigate antenatal care visit.Results: Out of 55 respondents, 26 had good knowledge, 25 had fair knowledge, and 4 had poor knowledge. Only 13 respondents had a good attitude level, while 42 had fair attitude, and none with poor attitude. As many as 46 respondents did antenatal care visits regularly, while 9 did not. Logistic regression analysis showed that knowledge and attitude had no significant influence towards regularity of antenatal care visit, with influence only approximately 2%. Conclusions: Knowledge, attitude, and regularity of antenatal care among respondents are good enough. Knowledge and attitude are not the dominant factors that affect the regularity of antenatal care visit. Thus a further study is needed to identify the other factors.